Application of the CARE guideline as reporting standard in the Annals of Research Hospitals - Office, Editorial (Annals of Research Hospitals, 2019)
The Annals of Research Hospitals welcomes case reports which are supposed to report new observations of diseases, clinical findings or novel/unique treatment outcomes relevant to practitioners in the fields of medicine.